AN ANALYSIS OF LINGUISTIC FEATURES ERRORS IN FACTUAL REPORT TEXT WRITING - Muhammad Nurhandika (Jurnal Ilmiah Spectral, 2026)
Indonesian students have a difficult time writing a genre text. Genre-based texts have specific linguistic features that must be adhered to, and violations of these features are frequently found in students' written work. Writing is widely considered the most demanding of the four language skills, as it requires not only grammatical accuracy but also the ability to organise ideas coherently, select appropriate vocabulary, and conform to genre-specific conventions. These demands become even more challenging for students learning English as a Foreign Language in the Indonesian context, where limited exposure to English and interference from Bahasa Indonesia further complicate the writing process. This study investigates the linguistic feature errors made by 19 eleventh-grade students at SMK Panca Bhakti Sungai Raya during the academic year 2019/2020 when writing factual report texts on the topic of domestic animals. A descriptive research design integrating qualitative and quantitative approaches was employed to collect and analyse the data. The findings reveal three dominant error categories: grammatical errors, which affected approximately 90% of students; substantive errors, present in all students' writing; and lexical errors, found in the majority of participants. The results suggest that students' limited vocabulary, unfamiliarity with English grammar rules, and insufficient mastery of genre-specific conventions are the primary contributing factors. These findings offer practical implications for more targeted and effective writing instruction in EFL vocational school classrooms.